2022
DOI: 10.7759/cureus.32226
|View full text |Cite
|
Sign up to set email alerts
|

Eye-Masks and Earplugs to Improve Night Sleep Duration in Nulliparas: A Randomized Trial

Abstract: BackgroundWomen experience significant sleep disruption throughout pregnancy. Lack of sleep during the last month of pregnancy is associated with longer labor, a higher rate of Cesarean births, gestational diabetes, hypertension, and preterm birth. Eye-mask and earplugs through sensory deprivation increase sleep duration and quality in patients in the intensive care environment but their impact at home or during pregnancy is not known. We sought to evaluate eye-mask and earplugs compared to sham/placebo headba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 25 publications
2
8
1
Order By: Relevance
“…The primary outcome, spontaneous vaginal delivery rate although higher in the EMEP arm, the result (RR 1.15 95% CI 0.88–1.51) was not significant. The observed effect of EMEP on this outcome was smaller than that from pilot data (RR 1.2 95% CI 0.9–1.9) we used from Teo et al [ 10 ] for sample size calculation. In our present trial the mode of delivery outcome metric that showed the highest magnitude point estimate was for the reduction in cesarean delivery (RR 0.78 95% CI 0.57–1.06) but this also did not reach significance.…”
Section: Discussionmentioning
confidence: 73%
See 4 more Smart Citations
“…The primary outcome, spontaneous vaginal delivery rate although higher in the EMEP arm, the result (RR 1.15 95% CI 0.88–1.51) was not significant. The observed effect of EMEP on this outcome was smaller than that from pilot data (RR 1.2 95% CI 0.9–1.9) we used from Teo et al [ 10 ] for sample size calculation. In our present trial the mode of delivery outcome metric that showed the highest magnitude point estimate was for the reduction in cesarean delivery (RR 0.78 95% CI 0.57–1.06) but this also did not reach significance.…”
Section: Discussionmentioning
confidence: 73%
“…Nulliparas (no prior pregnancy beyond 20 weeks), aged ≥ 18 years, singleton pregnancy between 34 to 36 weeks gestation with self-reported night sleep of less than 6 h [ 10 , 20 ] and access to the telephone were identified for recruitment in the antenatal clinic during their regular visits. In our center, all women booked to deliver in our hospital attend the antenatal clinic.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations